2005
DOI: 10.1038/sj.onc.1208832
|View full text |Cite|
|
Sign up to set email alerts
|

Wild-type blocking polymerase chain reaction for detection of single nucleotide minority mutations from clinical specimens

Abstract: Detection and sequencing of mutations from clinical specimens is often complicated by the presence of an excess of nonmutated cells. To facilitate the detection and sequencing of minority mutations from clinical specimens, we developed wild-type blocking polymerase chain reaction (WTB-PCR). This technique allows sensitive detection of minority mutations in a tissue sample containing excess wild-type DNA. In WTB-PCR, a nonextendable locked nucleic acid (LNA) oligonucleotide binds tightly to a region of wild-typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
83
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(84 citation statements)
references
References 11 publications
0
83
0
1
Order By: Relevance
“…This approach may prove useful when several mutations of interest occur in a given exon, although it remains to be seen how widely adaptable it is. The assay developed by McKinzie and Parsons 44 uses a blocking oligonucleotide to suppress priming of the wild-type allele. In our hands, addition of this type of blocker increased the sensitivity of the allele-specific PCR by more than 10-fold.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach may prove useful when several mutations of interest occur in a given exon, although it remains to be seen how widely adaptable it is. The assay developed by McKinzie and Parsons 44 uses a blocking oligonucleotide to suppress priming of the wild-type allele. In our hands, addition of this type of blocker increased the sensitivity of the allele-specific PCR by more than 10-fold.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a restriction endonuclease can be used to cleave wild-type sequence 44 showed that a blocking oligonucleotide that included locked nucleic acids substantially suppressed the amplification of wild-type BRAF exon 15 in an assay using Stoffel-fragment polymerase. This approach may prove useful when several mutations of interest occur in a given exon, although it remains to be seen how widely adaptable it is.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, there will only be extension of the mutant sequence, which can be detected using a fluorescently labeled primer. This assay has been successful in identifying SNPs in heterogeneous samples that contain excess wild type DNA [110]. The use of LNA probes in genotyping assays is an extremely promising tool for SNP characterization [105,109].…”
Section: High-resolution Melting (Hrm) Curve Analysismentioning
confidence: 99%
“…In addition to its use in delineating amplicons based on melting temperature differences, LNAs can be used to block oligonucleotide extension. This can be exploited for the identification of SNPs when a probe designed to target the region potentially containing the polymorphism is comprised of a LNA at its 3′ end [110]. The LNA is complementary only to the wild type nucleotide, which allows for the probe to anneal only if the sequence does not contain a polymorphism.…”
Section: High-resolution Melting (Hrm) Curve Analysismentioning
confidence: 99%
“…There has been particular interest in the innovation of PCR stages that enable nondestructive selection and enrichment of mutant alleles, as this can improve sensitivity and credibility of downstream assays, such as standard sequencing analysis. These recent enrichment PCR techniques include thermostable restriction endonuclease-mediated selective PCR, 6 PCR clamping mediated by peptide nucleic acid (PNA) 7,8 or locked nucleic acid (LNA), 9 and co-amplification at lower denaturation temperature PCR. 10 Each technique has its own strengths and limitations in regard to the cost, availability, or enrichment efficiency.…”
mentioning
confidence: 99%